Single strand confirmation polymorphism (SSCP) detection in exon I of the alpha -lactalbumin gene of Indian Jamunapari milk goats (Capra hircus) - Kumar, D; Gupta, N; Ahlawat, SPS; Satyanarayana, R; Sunder, S; Gupta, S C (Genetics and molecular biology, 2006)
The genetic diversity of Jamunapari goats (Capra hircus) was investigated using an optimized non-radioactive polymerase chain reaction single-strand conformation polymorphism (PCR-SSCP) method to detect alpha -lactalbumin polymorphism in a sample of 50 goats. Our data show that PCR-SSCP is an appropriate tool for evaluating genetic variability in Jamunapari goats. Polymorphism was detected in the sample, indicating that Jamunapari goats have high genetic variability at loci, exon I of the alpha -lactalbumin gene. This result opens interesting prospects for future selection programs and conservation strategies. These alpha -lactalbumin variants can be sequenced and screened in the population to develop single nucleotide polymorphism (SNP) markers for association studies and marker assisted selection.